Heterodimers of heterometallic rings. Issue 42 (1st August 2016) - Timco, Grigore; Marocchi, Simone; Garlatti, Elena; Barker, Claire; Albring, Morten; Bellini, Valerio; Manghi, Franca; McInnes, Eric J. L.; Pritchard, Robin G.; Tuna, Floriana; Wernsdorfer, Wolfgang; Lorusso, Giulia; et al.
Abstract : A supramolecular assembly of two molecular spin qubits is reported; they differ subtly in their g -values and the exchange interaction between them is measured and modelled. Abstract : Nine new complexes are reported involving linked heterometallic rings; one ring is designed as a ligand for the second, and the compounds produced can be regarded as molecular prototypes for implementing quantum gates featuring two subtly different qubits.